ECONOMIC RATIONALITY OF AGRICULTURAL ENTREPRENEURS IN BULGARIA - T. Taneva; N. Naydenova; P. Genova (Trakia Journal of Sciences)
The article presents the results of an empirical survey among entrepreneurs in the agrarian sector in Bulgaria. In view of the serious problems facing its development, the personal potential for entrepreneurial activity of economic agents is crucial for the future of the industry. Therefore, the problem of the rationality of economic decisions and economic behavior is significantly relevant. The main findings of the empirical study show that entrepreneurs have a high degree of rationality for decisions regarding purposefulness, analysis and decision-making, autonomy of intent for action, clarity, logic and consistency in actions. Less rationality is manifested in the prediction of consequences, the realization of the usefulness of business activity and the capabilities for its implementation, the realism, the consistency and the adaptability to circumstances. Overall, behavioral rationality is higher than the rationality of decisions. Subjective assessments of the economic risk of agrarian sector entrepreneurs are high, so preference is given to lower but secure profits. Educational level seems to be a very important factor for business success, but overall, agribusiness operators find it difficult to assess current market situation. There is satisfaction with profit accrued from their business and persistent intention to continue working with high subjective probabilities for success in future.